Holomorphology and neotype designation of Microperla retroloba (Wu, 1937) - Chen, Zhi-Teng; Du, Si-Kai; Jia, Xu; Liang, Ju-Pen; Yu, Ji-Hui (Zootaxa, 2021)
Microperla retroloba (Wu, 1937) is a poorly described species from Gansu Province of China and the types of which were apparently lost. Herein, a neotype of M. retroloba is designated based on new material from Ningxia Hui Autonomous Region adjacent to Gansu Province. Male, female, larva and egg morphology of M. retroloba are described, illustrated and compared with all congeners.